2014
DOI: 10.1186/1471-2164-15-445
|View full text |Cite
|
Sign up to set email alerts
|

Infection routes matter in population-specific responses of the red flour beetle to the entomopathogen Bacillus thuringiensis

Abstract: BackgroundPathogens can infect their hosts through different routes. For studying the consequences for host resistance, we here used the entomopathogen Bacillus thuringiensis and the red flour beetle Tribolium castaneum for oral and systemic (i. e. pricking the cuticle) experimental infection. In order to characterize the molecular mechanisms underpinning the two different infection routes, the transcriptomes of beetles of two different T. castaneum populations – one recently collected population (Cro1) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 63 publications
9
77
2
Order By: Relevance
“…3, Additional file 2: Figure S1). For example, 292 genes were up-regulated exclusively among larvae challenged with Btt (Control- Btt , Bt407 - - Btt and Btt - Btt ) and 307 were shared exclusively among Btt -challenged larvae that had not been primed or were primed with Bt407 - (Control- Btt and Bt407 - - Btt ), confirming a strong transcriptional response to Btt spore ingestion [19]. Interestingly, 315 genes were specifically up-regulated only in Btt -primed larvae ( Btt -Naive, Btt - Btt ), showing that Btt -priming drastically altered gene expression patterns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3, Additional file 2: Figure S1). For example, 292 genes were up-regulated exclusively among larvae challenged with Btt (Control- Btt , Bt407 - - Btt and Btt - Btt ) and 307 were shared exclusively among Btt -challenged larvae that had not been primed or were primed with Bt407 - (Control- Btt and Bt407 - - Btt ), confirming a strong transcriptional response to Btt spore ingestion [19]. Interestingly, 315 genes were specifically up-regulated only in Btt -primed larvae ( Btt -Naive, Btt - Btt ), showing that Btt -priming drastically altered gene expression patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Larvae were kept on the naive diet for 4 days after which they were similarly exposed to spore-containing (5 × 10 9 mL -1 Btt spores in PBS mixed with flour) or naive diet for 6 h and sampled for the transcriptome analysis. This timepoint was used since our previous study showed that sampling 6 h after the challenge gives a clear expression signature, compared to already weaker expression after 18 h [19]. Hence, the sampled treatments were as follows: Btt primed- Btt challenged ( Btt - Btt ), Bt407 - primed- Btt challenged ( Bt407 - - Btt) , Control- Btt challenged (Control- Btt ), Btt primed-Naïve ( Btt -Naive), Bt407 - primed-Naïve ( Bt407 - -Naïve), Control-Naïve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2008; Yokoi et al . 2012), and even characterized differences in gene expression between oral and septic challenge with Bt (Behrens et al . 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, individual immune priming by systemic injection would prove difficult in mass-reared insects due to their relatively small size and great number. In this context, the broad database available for other tenebrionid beetles is valuable because T. castaneum is considered as a model organism for the investigation of immune priming [134][135][136]. One advantage of T. castaneum is that oral priming is possible by adding pathogens or a corresponding supernatant directly to the diet [137].…”
Section: Immune Priming and Transgenerational Immune Primingmentioning
confidence: 99%